Toxic effects of carbon quantum dots on the gut–liver axis and gut microbiota in the common carp Cyprinus carpio. Issue 1 (29th November 2021) - Chen, Jianjun; Sun, Dandan; Cui, Han; Rao, Chenyang; Li, Lulu; Guo, Suqi; Yang, Shuai; Zhang, Yuru; Cao, Xianglin
Abstract : The potential toxicity of carbon quantum dots (CQDs) has received much attention because of their increasing biomedical applications. Abstract : The potential toxicity of carbon quantum dots (CQDs) has received much attention because of their increasing biomedical applications. However, the impacts of CQDs on the gut–liver axis and gut microbiota of the host remain unclear. In this study, we investigated the effects of CQD chronic exposure (5 weeks) on the biodistribution, histopathology, antioxidant capacity, immune response, lipid metabolism, and gut microbiota composition in the common carp Cyprinus carpio at different concentrations (2 and 20 mg kg −1 body weight). The results demonstrated that CQDs heavily accumulated in the intestine and liver, severely damaging these organs. Superoxide dismutase and glutathione were reduced and malondialdehyde was increased in intestinal and liver tissues, and the nrf2 / ho-1 signaling pathway was downregulated. In addition, CQDs activated toll-like receptor pathways to mediate inflammatory responses. Serum lipid levels were altered after CQD exposure, and srebp-1c, fas, hmgcr, and fxr expression was upregulated and cyp7a1 and cyp27a1 expression was downregulated in the intestine and liver. Interestingly, mttp and cpt-1α expression was upregulated and abca1, abcg8, and fgf19 expression was downregulated in the intestine, whereas their expression was opposite in the liver. Finally, 16S rRNA sequence analysis showed that gut microbiota diversity and richness were reduced, and the relative abundance of harmful bacteria increased and that of beneficial bacteria decreased. Bioinformatic analysis showed that the antioxidant capacity, immune response, and lipid metabolism also correlated with the relative abundance of gut microbial genera. In summary, this study provides reliable data for toxicological risk assessment of CQDs in aquatic ecosystems.